Expectation and perception of franchisee towards franchise business in Malaysia, 2007 / Affaniza Abu Karim - Abu Karim, Affaniza (Faculty of Business and Management, 2007)
Perbadanan Nasional Berhad (PNS) is the organization that provides their customers with service sector in financing. Their customers are Bumiputera Entrepreneur who is interested to involve in franchise business. Customers of PNS are including bumiputera franchisors and bumiputera franchisees. This research is done to study the franchisee expectation and perception towards franchise business in Malaysia. The objective of this study is to identify the expectation, perception and satisfaction of franchisee towards franchise business in Malaysia.